Studi Kerentanan Bangunan Akibat Gempa : Studi Kasus Perumahan Di Bantul - Bawono, Adi Setiabudi (Semesta Teknika, 2016)
One of earthquake mitigation activities is to know the probability of damage to buildings and the estimated loss caused by the earthquake on each typical building in an area. In developed countries attempt to predict the probability of damage to buildings caused by the earthquake have been found. One method used is a method of HAZUS (Hazard United States). In evaluating damage to buildings, one of the methods HAZUS by assessing the probability of damage to each building in an area using Fragility curve. In Indonesia, research on the Fragility Curve is still less. This study is an initial study to develop a Fragility curve which in turn will be compared with the version HAZUS Fragility curve building, so that it can be seen a typical residential buildings in Bantul, near the type of building whether in the United States. This study uses data reference damage to housing caused by the Yogyakarta earthquake May 27, 2006. Studied housing is housing that has the same type of building, which houses tembokan with retrofitting. Map data used mikrozonasi Bantul is a map Pariatmono (2008). The data collected includes data characteristic of houses and damage. House defects studied using media images or interviews with houseowners. To determine the probability of damage using FAHP (Fuzzy Analytic Hierarchy Process). Conclusions obtained from this study is that housing in Bantul are studied when compared with the type of building types URML tembokan HAZUS approach (Unreinforced Masonry Bearing Walls)